2020
DOI: 10.25103/jestr.131.14
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Notched Directional Blasting in Tensile Stress Field

Abstract: Notched blasting has been extensively applied as a traditional directional blasting method. At present, the measurement of notched blasting effect and rock fragmentation is mainly decided by the propagation behavior of blast-induced cracks. However, the influence of initial tensile stress field on such behavior is rarely considered in existing engineering blasting process, resulting in the non-remarkable directional fracture effect of tensile rock mass. To reveal the propagation behavior of the propagation beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Hu and Lu [8,9] studied the formation and propagation of crack induced by presplitting blasting in highly stressed rock mass via a mathematical model and concluded that the in situ stress can restrain the development of cracks between the presplitting holes when the in situ stress is perpendicular to the crack face. Yang and He [10,11] experimentally investigated the influence of confining pressure and ratios of horizontal-to-vertical pressure on the blast-induced rock fracture. The results showed that the direction of crack growth was largely controlled by the hoop tensile stress and biaxial pre-pressure ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Hu and Lu [8,9] studied the formation and propagation of crack induced by presplitting blasting in highly stressed rock mass via a mathematical model and concluded that the in situ stress can restrain the development of cracks between the presplitting holes when the in situ stress is perpendicular to the crack face. Yang and He [10,11] experimentally investigated the influence of confining pressure and ratios of horizontal-to-vertical pressure on the blast-induced rock fracture. The results showed that the direction of crack growth was largely controlled by the hoop tensile stress and biaxial pre-pressure ratio.…”
Section: Introductionmentioning
confidence: 99%